2011
DOI: 10.1177/1534734611418157
|View full text |Cite
|
Sign up to set email alerts
|

Differential Keratin Expression During Epiboly in a Wound Model of Bioengineered Skin and in Human Chronic Wounds

Abstract: Background Epiboly represents the process by which keratinocytes migrate to envelop a surface. We have been investigating a living bilayered skin construct (BSC) that is used in the treatment of lower extremity wounds due to venous insufficiency and diabetes. The construct demonstrates epiboly after injury and incubation in vitro, and this model may be useful for studying epidermal migration and the process of skin maturation. Punch biopsies of the construct in vitro were cultured and immunostained for specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
5
20
0
Order By: Relevance
“…Keratin 17 (K17), a type I intermediate filament, provides structural support for keratinocytes to maintain the functional integrity of epidermis (Windoffer et al, 2011). Although it is undetectable in normal epidermis, K17 expression is elevated in hyperproliferative states such as psoriasis and wound healing (Coulombe, 1997;Leigh et al, 1995;Luo et al, 2011). The discrepancy in the tissue distribution of K17 between normal and psoriatic epidermis suggests that K17 is an indicator of keratinocyte hyperproliferation and can be considered as a hallmark of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Keratin 17 (K17), a type I intermediate filament, provides structural support for keratinocytes to maintain the functional integrity of epidermis (Windoffer et al, 2011). Although it is undetectable in normal epidermis, K17 expression is elevated in hyperproliferative states such as psoriasis and wound healing (Coulombe, 1997;Leigh et al, 1995;Luo et al, 2011). The discrepancy in the tissue distribution of K17 between normal and psoriatic epidermis suggests that K17 is an indicator of keratinocyte hyperproliferation and can be considered as a hallmark of psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Cell counts showed twice as many IL‐6‐positive cells in the primed BSC as compared to the unprimed. CK17, a keratin protein that is prominently expressed in migrating epidermis after injury (Luo et al ., ), was also detected in the epidermal keratinocytes (Figure d–f). It is initially confined to the migrating basal cells when the epidermis is 1–2 cells thick (Luo et al ., ).…”
Section: Resultsmentioning
confidence: 75%
“…CK17, a keratin protein that is prominently expressed in migrating epidermis after injury (Luo et al ., ), was also detected in the epidermal keratinocytes (Figure d–f). It is initially confined to the migrating basal cells when the epidermis is 1–2 cells thick (Luo et al ., ). In our study, it showed an almost exclusive suprabasal location in the unprimed BSC but was detectable in both basal and suprabasal cells in the primed construct.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Keratin 10 is a marker of keratinocyte differentiation and maturation, so lack of expression at the tip of a migratory epidermal tongue is indicative of the dedifferentiated state of cells at the leading edge [58] . The same pattern of keratin 10 expression (no expression at the leading edge of the epidermal tongue) is observed in the empty control group at days 10 and 14 as the migratory front advances across the wound bed under the scab (Figure 7e, i).…”
Section: Immunohistochemical Evaluation Of Wound Healingmentioning
confidence: 99%